SP0101 Understanding the language of epidemiology articles. (12th June 2018) - Dixon, W.G.
Abstract : 'Clinical and Epidemiological Research' is one of two headings for original articles in the Annals of Rheumatic Disease. But what is epidemiological research? What do all those different types of bias mean? And what do all of those bizarre statistical terms mean? How can I make sense of the research, and how is it relevant to my practice? Answer: Attend the lecture and find out. Disclosure of Interest: W. Dixon Consultant for: Google, Bayer